2005
DOI: 10.1152/japplphysiol.01429.2004
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular infusions of plasma into fetal sheep cause arterial and venous hypertension

Abstract: Fetal volume control is driven by an equilibrium between fetal and maternal hydrostatic and oncotic pressures in the placenta. Renal contributions to blood volume regulation are minor because the fetal kidneys cannot excrete fluid from the fetal compartment. We hypothesized that an increase in fetal plasma protein would lead to an increase in plasma oncotic pressure, resulting in an increase in fetal arterial and venous pressures and decreased angiotensin levels. Plasma or lactated Ringer solution was infused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…This model of plasma infusion was developed to increase both fetal preload and afterload. As is illustrated by daily measurements (13), there is a gradual increase in mean fetal arterial pressure and central venous pressure with plasma infusion when compared with twin fetuses receiving the same volume of lactated Ringer solution. This model offers the unique opportunity to study the effects of both increased diastolic and systolic pressure load on the growing fetal heart.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…This model of plasma infusion was developed to increase both fetal preload and afterload. As is illustrated by daily measurements (13), there is a gradual increase in mean fetal arterial pressure and central venous pressure with plasma infusion when compared with twin fetuses receiving the same volume of lactated Ringer solution. This model offers the unique opportunity to study the effects of both increased diastolic and systolic pressure load on the growing fetal heart.…”
Section: Discussionmentioning
confidence: 95%
“…Consistent with our hypotheses, we found that the hearts of hypertensive fetuses were heavier than those of controls. This growth may be considered adaptive in that it permits fetuses to maintain biventricular stroke volume in the face of greatly increased arterial pressures (13). During the first 4 days of plasma infusion (early phase), there was a large increase in hemodynamic load and cardiac mass, such that the heart-tobody weight ratio increased by 30% compared with controls (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations